2008
DOI: 10.1093/sleep/31.4.569
|View full text |Cite
|
Sign up to set email alerts
|

Autonomic Arousals Related to Traffic Noise during Sleep

Abstract: Cardiac responses did not habituate to traffic noise within the night and may therefore play a key role in promoting traffic noise induced cardiovascular disease. If so, these consequences are more likely for responses accompanied by awakenings than for situations without awakenings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
84
2
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 108 publications
(95 citation statements)
references
References 26 publications
8
84
2
1
Order By: Relevance
“…The fact that cardiac arousals did not habituate across nights stresses their potential relevance for the genesis of longterm cardiovascular consequences of noise-induced sleep disturbance. 6,8,9 However, the noise-induced changes in heart rate SE refers to standard error; TST, total sleep time; *P < 0.05, **P < 0.01, ***P < 0.001 after controlling for a false discovery rate, i.e., the expected fraction of null hypotheses rejected mistakenly, of 0.05(*), 0.01(**), and 0.001(***), respectively.…”
Section: Event-related Analysismentioning
confidence: 99%
“…The fact that cardiac arousals did not habituate across nights stresses their potential relevance for the genesis of longterm cardiovascular consequences of noise-induced sleep disturbance. 6,8,9 However, the noise-induced changes in heart rate SE refers to standard error; TST, total sleep time; *P < 0.05, **P < 0.01, ***P < 0.001 after controlling for a false discovery rate, i.e., the expected fraction of null hypotheses rejected mistakenly, of 0.05(*), 0.01(**), and 0.001(***), respectively.…”
Section: Event-related Analysismentioning
confidence: 99%
“…By contrast, other studies have shown that different noise characteristics are of importance to predict the magnitude of the cardiovascular response. Berg et al (1975), Muzet (1980Muzet ( , 1992 and more recently Griefahn et al (2008) reported that significant heart rate increase can be observed even at relatively low noise intensities, indicating that the sleeping subject still perceives the external stimuli even if there is no awareness or memory of it the next day (Muzet 1992). Muzet (1980) showed that, during sleep, intermittent noise induces a rapid increase of heart instantaneous frequency (HIF) followed by a compensatory decrease, and a simultaneous peripheral vasoconstriction (Muzet 1980).…”
Section: Introductionmentioning
confidence: 99%
“…Haralabidis et al (2008) found that noise exposure during sleep elevated the subjects' blood pressure (BP). Similar negative effects of noise during sleep on heart rate (HR) have also been found (Griefahn, Bröde, Marks & Basner, 2007). In awake conditions, Lusk, Hagerty, Gillespie & Ziemba (2004) have shown that BP and HR were positively correlated with noise level (dBA) for industrial labourers, showing the undesirable effects of noise on cardiovascular health during work.…”
mentioning
confidence: 54%